ECONOMIC VALUATION OF ECOSYSTEM SERVICES OF A MULTIPURPOSE TROPICAL RESERVOIR: INSIGHTS FROM THE STANLEY RESERVOIR, INDIA - BHUTIA, TENJI PEM; QURESHI, NEHA WAJAHAT; P. S., ANANTHAN; CHRISPIN, C. LLOYD; S., KESAVAN; PANIKKAR, PREETHA (Journal of the Inland Fisheries Society of India, 2026)
Dams offer numerous advantages, particularly in addressing climate change challenges and meeting the rising global demand for electricity. However, recent experiences have revealed significant environmental, social, and political challenges associated with their construction. Despite their significance, ecosystem service (ES) assessments often overlook reservoirs created by dams and barrages in comparison to other inland aquatic systems. This study estimates the total economic value of the Stanley Reservoir, encompassing both use and non-use values. The study highlights five key services: fish production, agricultural output, domestic water supply, power generation, and tourism. Data collection involved household surveys and focused group discussions, which were analysed using market price-based approaches, the Contingent Valuation Method (CVM), and the Individual Travel Cost (ITC) method. The results show that the Stanley Reservoir generates about INR 62,620 million, or USD 753,66 million, in goods and services every year. The largest share of this value comes from power generation (79.71%), followed by agricultural production and irrigation (18.98%), tourism (0.55%), domestic water use (0.44%), and fisheries (0.25%). This study shows how important it is for the economy to value ecosystem services for long-term management and smart choices. It also shows how important Stanley Reservoir (also called Mettur Reservoir) is to the region’s growth.